PRESCRIBING PATTERN OF ANTIDIABETIC DRUGS AMONG DIABETIC INPATIENTS IN A TERTIARY CARE HOSPITAL - SOUMYA MARY ALEX,; UMA DEVI P, (International Journal of Pharma and Bio Sciences, 2016)
This prospective observational study examined the prescribing pattern of antidiabetic drugs in diabetic inpatients. The mean age of the patient population (n=104) was 60.9 years. Majority of the patients were male (77.9%) and in the age group of 61-70 years (40.4%). Diabetic foot complications (84.6%) were the most common co-morbid condition followed by hypertension (78.8%). Insulin was the most commonly prescribed drug during both hospital stay and at the time of discharge (95.2% and 91.3%, respectively) followed by metformin. During hospital stay, 77.9% patients were receiving monotherapy. Among insulin preparations, human neutral soluble insulin was most frequently prescribed. Hypoglycaemia was the most common adverse drug reaction reported. The prescribing trend is in compliance to current guidelines. Insulin thus appears to be the first line therapy in patients with diabetic foot complications, which was one of the most common reasons for hospitalization in the present study.